Cellular stress increases DRIP production and MHC Class I antigen presentation - Natalie Pach; Michael Basler; Michael Basler (Frontiers in Immunology, 2024)
BackgroundDefective ribosomal products (DRiPs) are non-functional proteins rapidly degraded during or after translation being an essential source for MHC class I ligands. DRiPs are characterized to derive from a substantial subset of nascent gene products that degrade more rapidly than their corresponding native retiree pool. So far, mass spectrometry analysis revealed that a large number of HLA class I peptides derive from DRiPs. However, a specific viral DRiP on protein level was not described. In this study, we aimed to characterize and identify DRiPs derived from a viral protein.MethodsUsing the nucleoprotein (NP) of the lymphocytic choriomeningitis virus (LCMV) which is conjugated N–terminally to ubiquitin, or the ubiquitin-like modifiers FAT10 or ISG15 the occurrence of DRiPs was studied. The formation and degradation of DRiPs was monitored by western blot with the help of a FLAG tag. Flow cytometry and cytotoxic T cells were used to study antigen presentation.ResultsWe identified several short lived DRiPs derived from LCMV-NP. Of note, these DRiPs could only be observed when the LCMV–NP was modified with ubiquitin or ubiquitin-like modifiers, but not in the wild type form. Using proteasome inhibitors, we could show that degradation of LCMV-NP derived DRiPs were proteasome dependent. Interestingly, the synthesis of DRiPs could be enhanced when cells were stressed with the help of FCS starvation. An enhanced NP118–126 presentation was observed when the LCMV-NP was modified with ubiquitin or ubiquitin-like modifiers, or under FCS starvation.ConclusionTaken together, we visualize for the first time DRiPs derived from a viral protein. Furthermore, DRiPs formation, and therefore MHC-I presentation, is enhanced under cellular stress conditions. Our investigations on DRiPs in MHC class I antigen presentation open up new approaches for the development of vaccination strategies.